FRI0528 Diagnostic Accuracy of MRI for Evaluating Early Sacroiliac Abnormalities in Juvenile Spondyloarthritis. (9th June 2015) - Bou Antoun, M.; Rossi-Semerano, L.; Guillaume-Czitrom, S.; Kone Paut, I.; Adamsbaum, C.
Abstract : Background: Juvenile spondyloarthritis (jSpA) encompasses a group of disorders characterized by similar clinical manifestations, namely peripheral arthritis and enthesitis, and genetic predisposition (HLAB27). Using the ILAR classification, jSpA includes enthesitis-related arthritis (ERA), juvenile psoriatic arthritis (jPsA) and undifferentiated arthritis. Only clinical signs, familial history and HLAB27 positivity but no imaging features are used in the ILAR classification. Limited data are available concerning the diagnostic accuracy of MRI to detect early sacroiliac joints changes in jSpA. Objectives: To describe early sacroiliac joints abnormalities with MRI in jSpA. Methods: This is a retrospective study conducted in a French reference centre for paediatric rheumatic diseases. The study involved patients who had a diagnosis of jSpA by a paediatric rheumatology expert since January 2006 to January 2015. Collected data included: age, gender, disease duration, clinical symptoms and signs (peripheral or axial involvement, extra-articular signs), biological inflammatory markers, HLAB27, plain radiographs and/or MRI made in the first three months after diagnosis. All radiographs and MRIs were analysed by two independent pediatric radiologists (one junior, one senior). Results: 85 patients (44 males, 41 girls), with a mean age of 11years (range 5-16) were included. Eighty-two out of 85 patients (96, 5%) had at least one X ray of a symptomatic joint (35 pelvic bones, 20 knees, 22ankles and 5 spinal joints). Seventy-eight plain radiographs were normal. We found non-specific abnormalities in 4 cases: indirect signs of effusion in 3 knees, and a L5-S1 spondylolysis. Among 51 patients who underwent a MRI of symptomatic joints in the first three months after diagnosis, 37 MRIs were fully available. Of 20 MRIs of hip and sacroiliac joints, we found a normal pattern in 10 cases (50%), mild bilateral (5) or unilateral (3) sacroiliitis (40%) and 2 hip synovitis. We didn't find any abnormalities in 2 spinal MRIs (1 cervical and 1 lumbar). We found pathological MRI features in peripheral joints: 7 out of 8 knees (3 synovitis and/or effusions, 1 tibial tuberosity enthesitis), and in 5 out 7 ankles (2 enthesitis of Achilles tendon, 1 tenosynovitis of medial ankle tendons, 1 bone marrow oedema (calcaneus), 1 synovitis). Conclusions: This study confirms that radiographs are not sensitive to detect sacroiliitis in the early stage of jSpA. Moreover, while the accuracy of MRI for the assessment of peripheral arthritis in children with JIA has been widely demonstrated, there is a lack of evidence about the diagnostic accuracy of MRI for evaluating early sacroiliac abnormalities in jSpA. Disclosure of Interest: None declared